EFFECT OF WELDING HEAT INPUT ON CORROSION RATE OF SPRINKLER IRRIGATION PIPING JOINTS BY TIG WELDING USED IN SOUTH OF IRAQ - & Fayyadh, Alwan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this experiment was to study effect of welding heat-input on microstructure and corrosion resistance of butt weld joint pipes in irrigation pipe used in South of Iraq. For this purpose, a single V-butt joint was carried out on low carbon steel pipes type (AISI 1005) welded in different parameters; welding current, welding voltage and heat input. The results are found, an increase of weld heat input lead to increase Widmanstatten ferrite (WF), acicular ferrite (AF) and polygonal ferrite (PF) phases in fusion zone (FZ) region. Also it is noted the Icorr of weld joint increases with increase of welding heat input, and subsequent increasing in corrosion rate, corrosion rate increased up to (0.0757µm/yr.) with increasing of heat input up to (5.151 KJ/mm).